Implementasi Teknologi Informasi dalam Pelayanan Pendidikan di MTs Negeri 02 Palembang - Devina Eka Putri, Poppy; Amilda, Amilda; Ibrahim, Ibrahim; Elyati, Eni; Zulkipli, Zulkipli (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study is based on the rapid development of information technology in the digital era, which has had a major impact on education, including in administrative services, learning, and school communication. The study aims to analyze the implementation of information technology in educational services at MTs Negeri 2 Palembang. It uses a descriptive qualitative approach with data collection techniques such as observation, interviews, and documentation. Research informants include the principal, administrative staff, and students. The data analysis techniques involve data collection, data presentation, verification, and drawing conclusions. The results and discussion show that information technology has been applied in various aspects of educational services at MTs Negeri 2 Palembang, such as student data management, the use of the e-Rapor application, and digital communication among teachers, students, and parents. However, this implementation still faces challenges such as limited infrastructure, lack of human resource training, and uneven internet access.